Transmission Dynamics of Zika Virus in Island Populations: A Modelling Analysis of the 2013–14 French Polynesia Outbreak - Kucharski, Adam J.; Funk, Sebastian; Eggo, Rosalind M.; Mallet, Henri-Pierre; Edmunds, W. John; Nilles, Eric J. (PLOS Neglected Tropical Diseases, 2016)
Author Summary Since the first reported major outbreak of Zika virus disease in Micronesia in 2007, the virus has caused outbreaks throughout the Pacific and South America. Transmitted by the Aedes genus of mosquitoes, the virus has been linked to possible neurological complications including Guillain-Barré Syndrome and microcephaly. To improve our understanding of the transmission dynamics of Zika virus in island populations, we analysed the 2013–14 outbreak on the six major archipelagos of French Polynesia. We found evidence that Zika virus infected the majority of the population, but only around 12% of total infections on the archipelagos were reported as cases. If infection with Zika virus generates lifelong immunity, we estimate that it would take at least 12–20 years before there are enough susceptible people for the virus to re-emerge. Our results suggest that Zika virus could exhibit similar dynamics to dengue virus in the Pacific, producing large but sporadic outbreaks in small island populations.